2002
DOI: 10.5694/j.1326-5377.2002.tb04670.x
|View full text |Cite
|
Sign up to set email alerts
|

General practice research: attitudes and involvement of Queensland general practitioners

Abstract: Objectives: To determine general practitioners' (GPs') attitudes towards and involvement in general practice research. Design: Postal survey and semi‐structured interviews conducted from May to September 2001. Participants and setting: 467 of 631 GPs in four Queensland Divisions of General Practice responded to the survey (74% response rate); 18 selected GPs were interviewed. Main outcome measures: Survey — attitudes to research; access to information resources; and involvement in research. Interviews — the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
99
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(107 citation statements)
references
References 13 publications
7
99
0
1
Order By: Relevance
“…Recruitment issues are echoed in other primary care research [28, 29]. Recruitment in primary care has particular challenges related to the characteristics of primary care practitioners, their patients and the dispersed nature of clinics [30].…”
Section: Discussionmentioning
confidence: 99%
“…Recruitment issues are echoed in other primary care research [28, 29]. Recruitment in primary care has particular challenges related to the characteristics of primary care practitioners, their patients and the dispersed nature of clinics [30].…”
Section: Discussionmentioning
confidence: 99%
“…The French healthcare system should implement this type of organization, already established and successful in the UK and in the Netherlands. Basing research questions on GPs’ expectations in a bottom-up approach can improve their participation in research projects [27]. Consulting patients on research projects using a community approach can facilitate their recruitment, as experienced in an Australian primary care research network.…”
Section: Discussionmentioning
confidence: 99%
“…According to those former results, relevance of the research topic, reimbursement and compatibility with routine general practice work are important factors. Ideally the GPs are embedded in an existing research culture [7,9,10]. Study nurses or mentors could be an important factor to enhance GPs' preparedness to participate in General Practice research because they reduce the administrative workload for GPs and enhance the motivation to participate in research [8,10,11].…”
Section: Discussionmentioning
confidence: 99%
“…An unexpected quantitative result of this study was that being involved with the training of medical students and being linked with the University is not reflected per se in a higher motivation in participating in research. Participating rates of about 30 % are usually achieved in random postal mailings to GPs without academic affiliation [5,9,13,14]. Previous studies have shown that involvement in student teaching represents a positive predictive factor for participation in research, so we assumed to achieve a much higher participation rate.…”
Section: Discussionmentioning
confidence: 99%